2015
DOI: 10.1007/s12603-015-0440-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of energy, nutrients and water in elderly people living at home or in nursing home

Abstract: The large individual differences (ranges) in energy, nutrients and water show that the use of mean values when analysing dietary intake data from elderly people is misleading. From a clinical perspective it is more important to consider the individual intake of energy, nutrients and water. Ageism is intrinsic in the realm of 'averageology'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 22 publications
5
28
0
1
Order By: Relevance
“…The nutritional status in homes for the elderly is different respective to community-dwelling elderly; specifically, elderly persons who live in senior facilities have been shown to have a lower BMI and/or MNA scores compared to those living in the community (p<0.05) 2,5,6 . Additionally, several studies compared nutritional status according to different types of homes, for example Strupeit et al 7 in Germany, that compared Home-living setting with Shared-housing arrangements (no risk according to MNA: 55.7% Vs. 16.6% respectively (p<0.001); van Nie-Visser et al 8 contrasted nursing home characteristics of three countries (Netherlands, Germany and Austria) and found differences by sex, age, length of stay, and dependency.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional status in homes for the elderly is different respective to community-dwelling elderly; specifically, elderly persons who live in senior facilities have been shown to have a lower BMI and/or MNA scores compared to those living in the community (p<0.05) 2,5,6 . Additionally, several studies compared nutritional status according to different types of homes, for example Strupeit et al 7 in Germany, that compared Home-living setting with Shared-housing arrangements (no risk according to MNA: 55.7% Vs. 16.6% respectively (p<0.001); van Nie-Visser et al 8 contrasted nursing home characteristics of three countries (Netherlands, Germany and Austria) and found differences by sex, age, length of stay, and dependency.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some researchers have used a single day of recalled (by resident or care staff) food intake to represent consumption patterns, resulting in potentially flawed conclusions on the adequacy of food intake [11–13]. Smaller studies with weighed food records, the gold standard, have demonstrated large inter-individual differences [12], but are commonly limited in measurement of covariates and the ability to model these due to the small sample size [12, 14]. Additionally, detailed descriptions of the food intake profile are often missing [15].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research on food intake is based on small, convenience samples (9)(10)(11)(12)(13)(14)(15) with relatively inaccurate methods for collecting intake, including relying on staff to record consumption (1,2,13,16) . Data on nutrient intake is not typically adjusted for intra-individual variation (1,2,13) nor is it based on a comprehensive panel of micronutrients (9,11,14,17,18) .…”
mentioning
confidence: 99%